Semiquantum Chaos in Two GaAs Quantum Dots Coupled Linearly and Quadratically by Two Harmonic Potentials in Two Dimensions - Emile Godwe; Justin Mibaile; Betchewe Gambo; Serge Y. Doka (Advances in Mathematical Physics)
We analyze the phenomenon of semiquantum chaos in two GaAs quantum dots coupled linearly and quadratically by two harmonic potentials. We show how semiquantum dynamics should be derived via the Ehrenfest theorem. The extended Ehrenfest theorem in two dimensions is used to study the system. The numerical simulations reveal that, by varying the interdot distance and coupling parameters, the system can exhibit either periodic or quasi-periodic behavior and chaotic behavior.